Photosynthetic activity of cassava plants under weed competition - Aspiazú,I. (2010)
The objective of this work was to evaluate characteristics associated with the photosynthetic activity of cassava plants under weed competition. The trial was carried out under field conditions, and experimental units consisted of 150 dm³ fiberglass boxes containing red yellow Latosol, previously corrected and fertilized. Treatments consisted in the cultivation of cassava plants which were free of weed competition and associated with three weed species: Bidens pilosa, Commelina benghalensis or Brachiaria plantaginea. After manioc sprouting started, 15 days after being planted, weeds that had been sown when manioc was planted were thinned, there were then eight plants left per experimental unit in accordance with specified treatments: cassava free of competition, cassava competing with B. pilosa, cassava competing with C. benghalensis and cassava competing with B. plantaginea. Sixty days after crop emergence leaf internal CO2 concentration (Ci), leaf temperature at the time of evaluation (Tleaf) and photosynthetic rate (A) were evaluated, also the CO2 consumption rate (ΔC) of cassava plants was calculated. A correlation matrix between variables was also obtained. All characteristics associated with photosynthesis in cassava plants were influenced by weed species. Cassava was more affected by B. pilosa and B. plantaginea in which concerns its exposition to solar radiation and water, while C. benghalensis seems to mostly affect the composition of incident light on the culture, allowing cassava to anticipate imposition when competing, even before it reaches harmful levels.